Coastal urbanization alters carbon cycling in Tokyo Bay - Atsushi Kubo (Nature Portfolio, 2020)
Abstract The carbon budget of Tokyo Bay, a highly urbanized coastal basin, was estimated using a box model that incorporated inorganic and organic carbon data over an annual cycle (2011–2012). The surface water represented net autotrophic system in which the annual net community production (NCP) was 19 × 1010 gC year−1. The annual loading of dissolved inorganic carbon and total organic carbon (TOC) from freshwater inputs was 11.2 × 1010 and 4.9 × 1010 gC year−1, respectively. The annual TOC sedimentation rate was 3.1 × 1010 gC year−1, similar to the annual air–sea CO2 uptake (5.0 × 1010 gC year−1). Although the NCP and TOC loading from freshwater inputs were respectively 3.0 and 2.7 times lower than those in the 1970s, the TOC sedimentation rate was similar. Therefore, a relatively high carbon efflux from Tokyo Bay likely occurred in the 1970s, including CO2 efflux to the atmosphere and/or export of labile organic carbon to the open ocean. The changes in carbon flow between the 1970s and 2011–2012 resulted from improved water quality due to increased sewage treatment facilities and improved sewage treatment efficiency in the catchment, which decreased the amount of labile organic carbon flowing into the bay.